Addressing the variation in adjuvant chemotherapy treatment for colorectal cancer: Can a regional intervention promote national change?. Issue 4 (10th September 2020) - Taylor, John C.; Swinson, Daniel; Seligmann, Jenny F.; Birch, Rebecca J.; Dewdney, Alice; Brown, Victoria; Dent, Joanna; Rossington, Hannah L.; Quirke, Philip; Morris, Eva J. A.; ,
Abstract: Analysis of routine population‐based data has previously shown that patterns of surgical treatment for colorectal cancer can vary widely, but there is limited evidence available to determine if such variation is also seen in the use of chemotherapy. This study quantified variation in adjuvant chemotherapy across both England using cancer registry data and in more detail across the representative Yorkshire and Humber regions. Individuals with Stages II and III colorectal cancer who underwent major resection from 2014 to 2015 were identified. Rates of chemotherapy were calculated from the Systemic Anticancer Treatment database using multilevel logistic regression. Additionally, questionnaires addressing different clinical scenarios were sent to regional oncologists to investigate the treatment preferences of clinicians. The national adjusted chemotherapy treatment rate ranged from 2% to 46% (Stage II cancers), 19% to 81% (Stage III cancers), 24% to 75% (patients aged <70 years) and 5% to 46% (patients aged ≥70 years). Regionally, the rates of treatment and the proportions of treated patients receiving combination chemotherapy varied by stage (Stage II 4%‐26% and 0%‐55%, Stage III 48%‐71% and 40%‐84%) and by age (<70 years 35%‐68% and 49%‐91%; ≥70 years 15%‐39% and 6%‐75%). Questionnaire responses showed significant variations in opinions for high‐risk Stage II patients with both deficient and proficient mismatch repair tumours and Stage IIIB patients aged ≥70 years. Following a review of the evidence, open discussion in our region has enabled a consensus agreement on an algorithm for colorectal cancer that is intended to reduce variation in practice. Abstract : What's new? Population‐based data have shown that surgery practice for colorectal cancer varies widely among different regions. Here, the authors delved into the population data to quantify the variation in adjuvant chemotherapy across England. They found a surprisingly high variation in chemotherapy rates for high‐risk stage II patients, and they suggest this difference results in part from clinicians' differing opinions about the effectiveness of chemotherapy for these patients. By highlighting the amount of regional variation in treatment practice, they achieved a consensus agreement on an algorithm they developed to provide standardized guidance for the use of chemotherapy.